Analisis Sistematis Hubungan Persepsi Mahasiswa terhadap Dosen dengan Motivasi Belajar - Mutiara Rizkiya; Agus Lestari (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
Variations in previous research findings regarding the relationship between students’ perceptions of lecturers and learning motivation indicate the need for a more comprehensive understanding. Several studies report strong influences of lecturers’ competence, teaching methods, and interpersonal interaction on students’ motivation, whereas others show weak or insignificant effects. To address these differences, this study conducts a Systematic Literature Review (SLR) following PRISMA guidelines through the stages of identification, screening, eligibility assessment, and inclusion. Relevant literature published between 2013 and 2023 was identified through Google Scholar using predetermined keywords and subsequently selected based on methodological rigor and thematic relevance. The synthesis results show that students’ perceptions of lecturers are shaped by pedagogical competence, instructional strategies, interpersonal communication, and the use of learning technology. Overall, positive student perceptions correlate with increased learning motivation in both face-to-face and online settings. However, this relationship is influenced by internal factors such as academic burnout and external factors such as the learning environment and technological readiness. These findings emphasize the importance of strengthening pedagogical competence, enhancing lecturers’ digital literacy, and creating supportive learning environments to improve students’ learning motivation. Keyword: Student perception, Lecturer competence, Learning motivation, SLR, PRISMA   Abstrak Variasi temuan dalam penelitian sebelumnya mengenai hubungan antara persepsi mahasiswa terhadap dosen dan motivasi belajar menunjukkan perlunya pemahaman yang lebih komprehensif. Beberapa studi melaporkan pengaruh kuat kompetensi dosen, metode mengajar, dan interaksi interpersonal terhadap motivasi belajar mahasiswa, sementara studi lain menemukan pengaruh yang lemah atau tidak signifikan. Untuk menjawab perbedaan tersebut, penelitian ini melakukan Systematic Literature Review (SLR) dengan mengikuti pedoman PRISMA melalui tahapan identifikasi, penyaringan, penilaian kelayakan, dan inklusi. Literatur relevan yang diterbitkan pada periode 2013–2023 diidentifikasi melalui Google Scholar menggunakan kata kunci yang telah ditetapkan, kemudian diseleksi berdasarkan ketepatan metodologis dan relevansi tematik. Hasil sintesis menunjukkan bahwa persepsi mahasiswa terhadap dosen dipengaruhi oleh kompetensi pedagogik, strategi pembelajaran, komunikasi interpersonal, serta pemanfaatan teknologi pembelajaran. Secara umum, persepsi positif mahasiswa berkorelasi dengan meningkatnya motivasi belajar, baik dalam pembelajaran tatap muka maupun daring. Namun, hubungan ini dipengaruhi oleh faktor internal seperti academic burnout dan faktor eksternal seperti lingkungan belajar serta kesiapan teknologi. Temuan ini menegaskan pentingnya penguatan kompetensi pedagogik, peningkatan literasi digital dosen, serta penciptaan lingkungan belajar yang mendukung dalam upaya meningkatkan motivasi belajar mahasiswa. Kata Kunci: Persepsi mahasiswa, Dosen, Motivasi belajar, SLR, PRISMA